An Analysis of Figurative Languages and Moral Values in Selected Songs of Shawn Mendes - Mitsalina, Endah; Fauziyah, Wasilatul; Nabila, Zulfa (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
There are many difficult to understand songs, especially when the lyrics contain a lot of figurative language and moral value within the song lyrics. It is not easy to understand without us analyzing the meaning of the song in depth. This research was conducted to identify the use of figurative language and the moral values contained in two songs by Shawn Mendes; ‘Stitches’ and ‘Believe.’ This research applied a qualitative method, and primary data was obtained from the two songs, while secondary data was obtained from journals, theses, books, and other sources on the internet. Data was collected through the documentation method. Based on the data analysis, the researchers found that the two songs contain three of figurative languages and three of moral values. The researchers found the use of 3 types of figurative language in the two songs, including: Hyperbole, Simile, and Symbol. As for the moral values, the researchers found 3 types of moral values in the two songs; Optimism, steadfastness, and love and compassion.